Diversity of Gut Microbes in Adult Vespa velutina (Asian Hornet) Carcasses Killed by Natural Causes - Meiling Pang; Ji Luo; Zhende Yang; Xuejian Jiang (Diversity, 2023)
[Objective] This study’s objective was to investigate the diversity of intestinal microorganisms in adult Vespa velutina (Asian hornet) killed by natural causes. This study investigates the composition of intestinal fungi and bacteria and predicts the pathogenic pathogen in adult Vespa velutina (Asian hornet). [Methods] We determined the ITS1 sequence of fungi and the V3–V4 variant region of 16S rRNA of bacteria using Illumina MiSeq technology. Operational taxonomic units (OTU) of gut symbiotic microorganisms were quantified, and the resulting data were subjected to analysis of species abundance, composition, and alpha diversity. OTU function was predicted using PICRUSt2/FUNGuild. In addition, cultured microorganisms from the gut microbiota of adult Vespa velutina were isolated and identified. A number of 3610 (fungi) and 8373 (bacteria) were identified via cluster analysis. A total of 13 strains, 51 classes, 126 orders, 285 families, and 586 genera were identified for fungi and 44 strains, 113 classes, 319 orders, 662 families, and 1394 genera were identified for bacteria. E. shigella, Herbaspirillum, and Aaaia were the most abundant classes of bacteria, and Fusarium, Mortierella, and Starmerella were the most abundant classes of fungi. In addition, 16 community genera of fungi and 11 of bacteria were outlined as core taxa. Species diversity and richness for the gut fungal and bacterial communities with VN were found to be higher than those with VA. Furthermore, bacterial species diversity and richness were found to be higher than those of fungi in VA and VN. Functional analysis revealed that Vespa velutina gut bacteria exhibited 20 functions, while fungi were classified into three types of nutrient modes. Cultivable bacteria were obtained from two phyla and two classes, but no fungi could be cultivated. [Conclusion] Variations in the species diversity and abundance of both fungi and bacteria in the gut were observed between the VA and the VN. The involvement of bacteria in the death of adult Vespa velutina was found to be significant. In addition, VA1 (the self-named strain) may be a pathogenic bacterium derived from the gut of the VA that exhibits virulence.